Hate Speech in Youtube Comments on Will Smith’s Oscars Speech 2022: A Pragmatic Study - Renita Raisya Anindya; Ervina CM Simatupang (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
The title of this research is "Hate Speech in YouTube Comments on Will Smith's Oscar Speech 2022: A Pragmatic Study." The purpose of this research is to identify the types of speech acts focusing on illocutionary acts, types of hate speech, and to describe the functions of illocutionary speech acts in YouTube comments about Will Smith's Oscar speech in 2022. In analyzing the data, the method used is descriptive qualitative method. The theory used in this research is the theory stated by Austin and further developed by Searle to identify the types of illocutionary speech acts and to identify the functions of illocutionary speech acts. This study analyzes 6 data points from YouTube comments about Will Smith's 2022 Oscar speech. The research shows that: 2 Assertives, 1 Commissives, 1 Expressives, 1 Directives, and 1 Declaration types and functions of illocutionary acts. Additionally, this research identifies 4 types of hate speech in the form of insults, 1 type of unpleasant action, and 1 type of provocation. These findings help reveal how hate speech is constructed linguistically and how illocutionary acts contribute to shaping negative narratives online. This analysis is expected to provide insights into the relationship between speech acts and digital communication, especially in the context of viral or controversial matters.